Development of Learning Media Video Interactive Basic Motion Volleyball Game by Edpuzzle - Nevi Hardika; Muhammad Suhairi; Henry Maksum; Suhartini Suhartini; Adiyudha Permana (AL-ISHLAH: Jurnal Pendidikan, 2024)
The quality of education is significantly influenced by the implementation of high-quality learning processes by teachers, supported by technology, to prepare an advanced and excellent younger generation towards the Golden Years. Integrating technology-based media, such as Edpuzzle, into educational materials can enhance the learning experience. This study explores the application of Edpuzzle in teaching volleyball to improve educational outcomes. The research employs the Research and Development (RD) ADDIE model, which encompasses five phases: analysis, design, development, implementation, and evaluation. This comprehensive approach involves collaboration with media experts and subject matter experts to ensure the quality and relevance of the developed educational media. The study resulted in the creation of an interactive multimedia learning product using the EdPuzzle application for volleyball materials. This product incorporates various multimedia elements, including videos, sound, text, images, and questions, structured in a way that follows educational syntax such as material concepts and activity phases. The effectiveness of this product was assessed through user reviews from students, who gave it an average score of 93.8%, categorizing it as excellent. The findings indicate that the EdPuzzle-based interactive multimedia learning product is highly effective in teaching volleyball. The high user review score suggests that students find this method of learning enjoyable and beneficial. The multimedia elements and interactive features likely contribute to a more engaging and efficient learning experience. The research concludes that the EdPuzzle-based interactive multimedia learning product is feasible and effective as a learning resource for volleyball materials. This technology-enhanced approach not only improves the quality of education but also makes the learning process more enjoyable and efficient. Therefore, it can be recommended for broader use in educational settings to support the development of an advanced and excellent younger generation.